Hibiscus sabdariffa L. and Its Bioactive Constituents Exhibit Antiviral Activity against HSV-2 and Anti-enzymatic Properties against Urease by an ESI-MS Based Assay - Hassan, Sherif T S; Švajdlenka, Emil; Berchová-Bímová, Kateřina (Molecules (Basel, Switzerland), 2017)
For decades, Hibiscus sabdariffa L. and its phytochemicals have been shown to possess a wide range of pharmacologic properties. In this study, aqueous extract of Hibiscus sabdariffa (AEHS) and its bioactive constituent protocatechuic acid (PCA), have been evaluated in vitro for their antiviral activity against HSV-2 clinical isolates and anti-enzymatic activity against urease. Antiherpetic activity was evaluated by the titer reduction assay in infected Vero cells, and cytotoxicity was evaluated by the neutral red dye-uptake method. Anti-urease activity was determined by a developed Electrospray Ionization-Mass Spectrometry (ESI-MS)-based assay. PCA showed potent anti-HSV-2 activity compared with that of acyclovir, with EC50 values of 0.92 and 1.43 µg∙mL-1, respectively, and selectivity indices > 217 and > 140, respectively. For the first time, AEHS was shown to exert anti-urease inhibition activity, with an IC50 value of 82.4 µg∙mL-1. This, combined with its safety, could facilitate its use in practical applications as a natural urease inhibitor. Our results present Hibiscus sabdariffa L. and its bioactive compound PCA as potential therapeutic agents in the treatment of HSV-2 infection and the treatment of diseases caused by urease-producing bacteria.
Keywords: Animals; Antiviral Agents; ureasa; Chlorocebus aethiops; acyklovir; Kinetics; Inhibitory Concentration 50; antivirové látky; Herpesvirus 2, Human; urease inhibitors; rostlinné extrakty; Polyphenols; Vero Cells; vysokoúčinná kapalinová chromatografie; Enzyme Inhibitors; Acyclovir; protocatechuic acid; Vero buňky; Hibiscus sabdariffa L.; inhibiční koncentrace 50; lidský herpesvirus 2; Urease; bacterial infection; Drug Evaluation, Preclinical; hmotnostní spektrometrie s elektrosprejovou ionizací; preklinické hodnocení léčiv; Chromatography, High Pressure Liquid; anti-HSV-2 activity; inhibitory enzymů; Hibiscus; Plant Extracts; polyfenoly; Cercopithecus aethiops; zvířata; Spectrometry, Mass, Electrospray Ionization; ESI-mass spectrometry-based assay; kinetika